Pusa Rasdar: New variety of bitter gourd suitable for protected cultivation - Behera, T K; Munshi, A D; Singh, A K (Indian Horticulture, 2023)
Pusa Rasdar is first open pollinated variety of bitter gourd suitable for growing in insect-proof net house during spring summer (February-June) and kharif (July-November) and under polyhouse during winter season (November-March). It is non-parthenocarpic, predominately gynoecious and produces 1-2 lateral branches. It is extra early (43-47 days for first fruit harvest) variety suitable for cultivation under protected condition throughout the year. It requires hand pollination when grown under protected conditions. Fruits are juicy with anti-diabetic properties like saponin (40-45 μg/g) and charantin (35-40 μg/g) and can be used as health drinks. The average fruit weight is 110 g with average yield of 4.7 q/100 sqm insect proof net-house and 4.0 q/100 sqm polyhouse. It has been released and notified by the Central Sub-Committee on Crop Standards, Notification and Release of Varieties for Horticultural Crops for cultivation in National Capital Region of Delhi and its adjoining states.